Grazing characteristics in the dwarf Elephantgrass (Pennisetum purpureum Schumach) pasture by breeding beef cows at the first and second years after establishment - Mukhtar, Muhammad (Indonesian Journal of Animal and Veterinary Sciences, 2007)
In order to determine grazing characteristics in the dwarf Elephantgrass pasture under the rotational grazing system, 5 a of pasture established by rooted tillers of dwarf variety of late-heading type (DL) was grazed by 3 head of breeding beef cows in the following 2 years after establishment in 2003 and 2004. Grazing system was conducted at 4 and 5 times for about 1-week grazing with 3-weeks and 1-month rest period in 2003 and 2004, respectively. Tiller number increased seasonally from the first through the fourth or fifth grazing, and herbage dry matter weight reached the peak at the fourth grazing both years, while some characters such as plant height, mean tiller dry matter weight and percentage of leaf blade tended to decrease with the grazing. From the stratified clipping method, percentage leaf blades in the top two, third and in the fourth strata were consumed perfectly and almost perfectly, respectively both years. Herbage consumption increased with the grazing up to the third and fourth grazing and dropped at the last grazing due to the poor regrowth under the decreasing air temperature both years. Dry matter intake per head averaged 4.3â13.4 kg DM head-1 day-1 in 2003 and 6.7-11.4 kg DM head-1 day-1 (15.5-28.6 g DM/kg LW-1 day-1) in 2004. Grazing time on DL elephantgrass was stable at 50â60% in daytime at the first grazing day both years, while that at the last grazing day tended to increase with the grazing both years. Thus, live weights of 3 head of beef cows were maintained in the grazing from the second to the fourth time without concentrate feeding in 2004, when dry matter intake was above 20 g DM Â LW-1 day-1. Key Words: Dwarf-Elephantgrass, Grazing Characteristics, Beef Cows, Percentage Leaf of Blade